IMPROVING THE USE OF MODERN INFORMATION TECHNOLOGIES IN COMMERCIAL BANKS - Axmedova Dilafruz Elshodovna (Scholar Express Journals, 2022)
Digital banking technologies and their content and elements are widely covered in the article. The scientific views of foreign and local scientists on banking technologies have been deeply studied, analyzed and author's opinions have been expressed. In addition, scientifically based proposals have been developed for the effective use of banking technologies and further improvement of their efficiency
Keywords: Banking technologies; information technologies; mobile banking; credit